2016
DOI: 10.1177/1457496916668681
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Surgical Site Infection with Negative-Pressure Wound Therapy After Open Abdominal Surgery: A Prospective Randomized Controlled Study

Abstract: Negative-pressure wound therapy can reduce the incidence of surgical site infection in open abdominal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 31 publications
0
74
0
1
Order By: Relevance
“…A meta‐analysis of Semsarzadeh and colleagues indicated SSSI rates after abdominal surgery of 0% (cesarean section; 8.3% with SSD) to 20.4% (ventral hernia; 25.8% with SSD) . Li et al reported SSSI rates of 4% (iNPWT) vs. 31% (SSD; p = 0.028) in patients undergoing abdominal surgery . Blackham et al announced SSSI rates of 6.7% (iNPWT) vs. 17.2% (SSD) ( p = 0.035) in patients operated due to abdominal carcinoma .…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis of Semsarzadeh and colleagues indicated SSSI rates after abdominal surgery of 0% (cesarean section; 8.3% with SSD) to 20.4% (ventral hernia; 25.8% with SSD) . Li et al reported SSSI rates of 4% (iNPWT) vs. 31% (SSD; p = 0.028) in patients undergoing abdominal surgery . Blackham et al announced SSSI rates of 6.7% (iNPWT) vs. 17.2% (SSD) ( p = 0.035) in patients operated due to abdominal carcinoma .…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines on antibiotic prophylaxis provide recommendations for selection of the appropriate antimicrobial for each surgical intervention [28]. However, the antibiotic is not always enough to reduce the virulence for bacterial (very often polymicrobial) in infecting the surgical sites very often it is necessary to resort to advanced medications such as vac, silver dressings and etc [21,29]. Without a doubt the difference in results between children and the elderly in skin healing is due to a biological-anatomical factor.…”
Section: Discussionmentioning
confidence: 99%
“…One of the potential solutions that could help to achieve these goals may be the extensive and early use of Negative Pressure Wound Therapy (NPWT) devices in the prevention of wound healing complications 3 (mainly surgical site infections -SSI 4 or wound dehiscence), particularly among higher-risk patients, 5 those with complex incisions with ort without prosthetic devices underlying the closed incision. [6][7][8] Li et al proved that patients undergoing NPWT after open abdominal surgery had SSI less frequently 9 and the formation of enteroatmospheric fistulae were also less frequent in patients receiving. 10 The relative liberal use of ciNPWT, may well be advantageous for patients who are discharged as an inpatient earlier than normal to free up capacity for acute COVID beds may continue to receive good quality healthcare at home.…”
Section: General Strategymentioning
confidence: 99%